Pengaruh Return On Asset dan Earning Per Share terhadap Harga Saham pada Industri Kosmetik Dan Keperluan Rumah Tangga yang Terdaftar di Bursa Efek Indonesia (Bei) Periode 2016-2020 - Nur Sri Fakhzilla (Science of Management and Students Research Journal (SMS), 2021)
The purpose of this study is to find out and analyze the effect of return on asset (ROA) and earnings per share (EPS) simultaneously on the stock price in the Cosmetics Industry and Household Needs Listed on the Indonesia Stock Exchange (IDX) and To find out and analyze the effect of return on asset (ROA) and earnings per share (EPS) partially on the stock price on the Cosmetics Industry and Household Needs Listed on the Indonesia Stock Exchange (IDX). This research includes a type of correlational research, using the research method used is the survey method. The technique of retrieving the data with a questionnaire, the score obtained from the questionnaire is then analyzed with descriptive analysis poured in the form of percentages. The results of calculations using the spss program by comparing fhitung with ftabel with a significant level of α = 0.05. It can be known that the fhi calculate of 14,096 by comparing the ftabel α = 0.05 with the degree of free numerator (the number of X) = 4 and the degree of denominator (N-K-1) = 28, obtained ftabel of 2.74. The calculation is greater than that of ftabel (14,096 > 2.74) then Ho is rejected and Ha is accepted, meaning there is a significant influence between independent variables (x) together against dependent variables (y). Which means that simultaneously independent variables ROA and EPS affect the dependent variables of stock prices. Based on the results of the t (partial) test on the regression model, the comparison between thitung and ttabel shows thitung as large as (1,069) while the ttabel is 1,996. From the results it can be seen that thitung > ttabel that is (1,069) < 1,996 it can be concluded that Ho received Ha rejected means that partially the VARIABLE ROA positively affects the Stock Price The comparison between thitung and ttabel which shows thitung of 2,696 while>> the ttabel of 1,996. 1996, it can be concluded that Ho received Ha rejected meaning that partially the EPS variable has a positive and significant effect on the variable stock price. Based on the results of the determination coefficient test in the table above, it shows that the value of R Square is 0.511 which means that the amount of the contribution of independent variables namely X1 ROA, X2 EPS, affects variable Y Share Price by (0.511 x 100 = 51.1%), while the rest (100% - 51.1% = 48.9%) is influenced by other variables outside of this study.